The Slow Garden: Gardening as Deceleration - Roeland, Johan Hendrikus (Cross currents, 2023)
Much more than a hobby or a leisure activity, gardening is for many gardeners a way of creating a place that escapes our contemporary culture of speed. As a counterpart to acceleration that strongly defines the late modern human condition, resulting in feelings of business, stress and haste, the garden offers a slow zone in which a regime of time operates that differs from the regime of clock time that dominates everyday life. Gardening thus offers an opportunity to find balance in an accelerating world.